The effects of revegetation in the natural environment and perception of the people linked to Camero Viejo (Iberian System) - Teodoro Lasanta Martínez; Estela Nadal-Romero; Pili Serrano-Muela (Boletín de la Asociación de Geógrafos Españoles)
The perception of the population linked to Cameros Viejo (Iberian System) about the revegetation process and its impacts on the natural environment is studied. We carried out 40 depth semi-structured interviews. The interviewee’ answers are corroborated with the results of scientific works carried out in the study area and in other nearby areas of the Mediterranean mountains. Moreover, it is observed that the local population shows a more realistic perception than the foreign population about the changes in the natural environment